Theoretical and Methodological Approaches to the Study of the Territorial System of Monodevelopment in Geographical Space - Смочко, Наталія Михайлівна (Київський національний університет імені Тараса Шевченка, 2020)
The purpose of this research work is to analyze modern theoretical and methodological approaches to the study of territorial systems of monodevelopment in the theory of social geography. Method. General scientific methods, including analysis, scientific synthesis, analytical method, methods of comparison and generalization were used in the study. Scientific novelty. The article reveals traditional and innovative approaches to identifying and defining the territorial system of mono-development in the geographical space. In substantiating the application of approaches, we used the work of scientists and geographers, who took them into account in the study of complex systems. It has been determined that the leading and traditional approaches in socio-geographical research are historical-geographical (retrospective) and territorial (geospatial), which should be combined with genetic. According to which all geographical phenomena have been considered as processes that have their genesis, dynamics, differences, patterns spatial distribution. To study the processes of system formation, a comprehensive approach is important. It provides a comprehensive analysis of the development of the main factors in the formation of modern socio-economic processes in the regions. The system approach allows to consider functioning and development of the territorial monosystem and its basic types as systems of the territorial organization of a society at various hierarchical levels, to open their integrity and the mechanisms providing effective management of such monodevelopment. At the same time, it has been found that not all the outlined approaches of complex systems can be used to study monosystems in the form in which they were used previously. This is because in the study of systems in retrospect, the application of approaches was focused on the analysis of the structure of the studied objects and the variety of processes that took place between the elements of the studied systems. In the study of monosystems, the researcher should be interested in their development to bifurcation moments and the conditions for further preservation of monosystems. This means that traditional approaches, such as historical-geographical (retrospective) and territorial (geospatial) should be modified to adapt to these tasks. It is important to use innovative approaches: cluster (formation of so-called network structures), behaviorist (explanation of the territorial identity of the monosystem), participatory (strategic planning of the territorial development of the monosystem). Only by combining a variety of approaches will it be possible to obtain a synergistic effect and form a synergistic approach that will provide additional benefits in the study of monosystems and the processes of their functioning. Practical meaning. The results of this study contribute to a deeper socio-geographical understanding of the processes of monodevelopment, their genesis, features of their course and provide an opportunity to model the long-term development of territorial social systems, to achieve expected results due to long-term transformation. They can be used for further study of monosystems of different hierarchical levels, as well as for the development of practical recommendations and programs for the development of individual monoterritories.

Метою даної роботи є аналіз сучасних теоретико-методологічних підходів до вивчення територіальних систем монорозвитку в теорії суспільної географії. Методика. В дослідженні використані загальнонаукові методи, зокрема аналіз, науковий синтез, аналітичний метод, методи порівняння та узагальнення. Наукова новизна. В статті розкрито традиційні та інноваційні підходи до виявлення та визначення територіальної системи монорозвитку в географічному просторі. При обґрунтуванні застосування підходів нами використано напрацювання вчених географів, що бралися ними до уваги при дослідженні складних систем. Визначено, що провідними і традиційними підходами у суспільно-географічних дослідженнях посідають історико-географічний (ретроспективний) та територіальний (геопросторовий), які доцільно поєднувати з генетичним, за яким усі географічні явища розглядають як процеси, що мають свою ґенезу, динаміку, відмінності, закономірності просторового поширення. Для вивчення процесів системоформування важливе значення має комплексний підхід, що передбачає всебічний аналіз розвитку основних чинників формування сучасних соціально-економічних процесів у регіонах. Системний підхід дозволяє розглядати функціонування і розвиток територіальної моносистеми та її базових типів як систем територіальної організації суспільства на різних ієрархічних рівнях, розкрити їх цілісність і механізми, що забезпечують ефективне управління таким монорозвитком. При цьому нами встановлено, що не всі окреслені підходи складних систем можна використовувати для вивчення моносистем у такому вигляді у якому вони використовувалися раніше. Це пов’язано з тим, що при вивченні систем в ретроспективі застосування підходів було орієнтоване на аналіз структури досліджуваних об’єктів та на різноманітті процесів, які відбувалися між елементами досліджуваних систем. При дослідженні моносистем, дослідника повинно цікавити їх розвиток до біфуркаційних моментів і умови подальшого збереження моносистемності. Це означає, що традиційні підходи, такі як історико-географічний (ретроспективний) та територіальний (геопросторовий) доцільно модифікувати, з метою адаптації для виконання цих завдань. Важливо використовувати й інноваційні підходи: кластерний (формування так званих мережевих структур), біхевіористський (пояснення територіальної ідентичності моносистеми), партисипативний (стратегічне планування територіального розвитку моносистеми). Тільки при поєднанні найрізноманітніших підходів можна буде отримати синергетичний ефект та сформувати синергетичний підхід, який дозволить передбачити додаткові вигоди при дослідженні моносистем і процесів їх функціонування. Практичне значення. Результати даного дослідження сприяють глибшому суспільно-географічному розумінню процесів монорозвитку, їх генезису, особливостей їх протікання та дають можливість моделювати перспективний розвиток територіальних суспільних систем, досягати очікуваних результатів внаслідок довготривалої трансформації. Вони можуть бути використані для подальшого дослідження моносистем різного ієрархічного рівня, а також для розробки практичних рекомендацій та програм розвитку окремих монотериторій.
Теоретико-методологічні підходи до вивчення територіальної системи монорозвитку в географічному просторі
Keywords: методологічні підходи; територіальна система монорозвитку; монотериторія; методологические подходы; территориальная система моноразвития; монотерритория; methodological approaches; territorial system of monodevelopment; monoterritory